Impact of forced migration on the sustainable development of rural territories - V. Shcherbak; I. Brizgan; V. Chevhanova; L. Svistun; O. Hryhoryeva (Global Journal of Environmental Science and Management)
This study provides a comprehensive scientific analysis of contemporary problems resulted from the forced migration of the Ukrainian population and its impact on the sustainable development of 47 host communities of Poltava region. By means of cluster analysis 4 clusters of 26 rural territories were identified. They differ in the size of local budgets and the involvement level of forcedly displaced population into the local economy. Factor analysis showed that the involvement level of forcedly displaced population in the region's economy is determined by 2 groups according to 10 indicators. 8 indicators of the first factor determine 2/3 of the dispersion of refugees' impact on rural economy. The first factor reduces the gross regional product by 61.75%. The indicators of the second factor shows a positive impact and determines 15% of the dispersion. The use of game theory to identify conflicts of interest between refugees and host communities was justified. The reasonability to use the taxonomy method to construct a map of positioning rural areas according to the size of local budgets and the degree of integration of refugees is justified. The use of the created map identified the “growth points” in particular clusters. As a result of the implementation of the proposed conflict resolution mechanism between refugees and host communities, the budget of the rural areas of the first cluster increased by 18%, the second cluster by 14.5%, the third cluster by 13%, the fourth by 8%, refugee participation by 30%.